Evaluation of a beach volleyball skill instrument for the line shot attack - Giatsis, G.; Lola, A.; Hatzimanouil, D.; Tzetzis, G. (Journal of Physical Education, 2024)
This study aimed to develop a test for measuring athletes` performance. Logical, content, construct, criterion validity, as well as reliability, were examined. Three beach volleyball experts evaluated how well the test evaluates the shot skill accuracy according to their judgment (logical validity). A group of eight beach volleyball experts analyzed the test and rated it on a scale of 1 to 7 regarding the relevance of the content as a measure of beach volleyball athlete`s accuracy, the average score was calculated at 6.75 (SD=0.46) (content validity). 60 beach volleyball players divided into three equal groups of novices, intermediates, and experts were asked to undergo the test on two separate days. A one-way ANOVA between the three groups was performed, which indicated that the mean scores of the three groups differed significantly (p<0.001 for both days): experts achieved better scores than intermediates who in turn scored better than novices (construct validity). The athletes` scores were correlated with their proficiency level, using the Pearson Correlation test, which indicated very high positive (Day-1: r=0.956, n=60, p<0.001; Day-2: r=0.953, n=60, p<0.001) (criterion validity). The intraclass correlation coefficient was calculated between Day-1 and Day-2 and was found equal to 0.980 for average measures (p<0.001) and 0.961 for single measures (p<0.001). In conclusion, the requirements for logical, content, construct, criterion validity, and reliability have been met. Therefore, the line shot attack test can be used as a valid and reliable measurement instrument for evaluating the performance of beach volleyball athletes.